Pengaruh Kualitas Layanan Terhadap Tingkat Kepuasan Masyarakat Pada Program Budayakan Arsip Keluarga Menjadi Dokumen Berharga(BASIKAMEH) Di Dinas Perpustakaan Dan Kearsipan Kota Solok Provinsi Sumatera Barat - Endah Fauziah Giska; Jeihan Nabila (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The purpose of this study is to describe (1) the quality of service in the BASIKAMEH program, (2) the level of community satisfaction in Solok City, (3) the effect of BASIKAMEH program service quality on the level of community satisfaction in Solok City. This research is a quantitative research with descriptive method. This study took 57 respondents who were participants in the BASIKAMEH program. The sampling technique in this study used simple random sampling using the Slovin formula. The data collection techniques used were observation, questionnaires (questionnaires), and also unstructured interviews. The results of this study indicate that the service quality variable gets an average value of 3.19 which is in the